Preparation of MoS2-based polydopamine-modified core–shell nanocomposites with elevated adsorption performances. Issue 38 (13th June 2018) - Sun, Shuxin; Jiao, Tifeng; Xing, Ruirui; Li, Jinghong; Zhou, Jingxin; Zhang, Lexin; Peng, Qiuming
Abstract : New core–shell MoS2 –PDA nanocomposites are prepared via mussel-inspired chemistry and a simple interfacial self-assembly process, demonstrating potential applications in wastewater treatment and self-assembled core–shell composite materials. Abstract : New molybdenum disulfide (MoS2 )-based core–shell nanocomposite materials were successfully prepared through the self-assembly of mussel-inspired chemistry. Characterization by Fourier transform infrared, thermogravimetric analysis, scanning electron microscope and transmission electron microscopy revealed that the surface of the flaked MoS2 was homogeneously coated with a thin layer of polydopamine (PDA). Dye adsorption performances of the synthesized MoS2 –PDA nanocomposites were investigated at different pH values and reaction times. Compared with pure MoS2 nanosheets, the obtained core–shell nanocomposites showed elevated adsorption performances and high stability, indicating their potential applications in wastewater treatment and composite materials.